The Influence of Leadership and Empowerment on The Performance of Employees in the Transportation and Passenger Facilities Section at PT. KAI (persero) Divre III Palembang - April Riska; Meilin Veronica; Emilda (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to analyze the influence of leadership and empowerment on employee performance at PT.KAI (Persero) Divre III Palembang. In this study it was collected by distributing questionnaires to 60 respondents. Data collection techniques in the form of interviews and descriptive data analysis techniques with a quantitative (statistical) approach to variable data and multiple regression analysis. The research instrument uses validity and reliability tests. Hypothesis testing using the t test and f test. The results of this partial research show that Leadership has a significant effect on employee performance with a significant value (0.023 <0.05), so statistically at a significant level of 5% (0.05), it can be stated that the partial hypothesis H2 is proven and accepted. Empowerment has a significant effect on employee performance with a significant value (0.016 <0.05), then statistically at a significant level of 5% (0.05), it can be stated that the partial hypothesis H2 is proven and accepted. Leadership and empowerment have a significant effect on employee performance. The correlation coefficient value obtained was 40.4 and the determination coefficient value obtained was 16.3 percent indicating that there is a relationship between leadership and empowerment on employee performance.